Ciprofloxacin Susceptibility Pattern in a Secondary Health Care Facility in Kebbi State, Nigeria - & Usman K., Ajibola O., Aliyu B. (Covenant Journal of Physical and Life Sciences, 2018)
Antibiotic resistance is a major challenge in management of infectious diseases globally, and particularly in developing countries. There are few studies that have analysed the impact of such abuse on the development of bacterial resistance in Nigeria and sub Saharan Africa. To this end, we retrospectively analysed ciprofloxacin susceptibility patterns in a secondary healthcare facility in Northwest Nigeria over a four year period. Three hundred and thirty six pathogens isolated from 370 patients were analysed in this study. The common pathogens isolated from wound infections were Staphylococcus aureus (29, 7.84%), Pseudomonas spp (10, 2.7%) and Proteus spp (7, 1.89%). In stool samples, Proteus (11, 2.97%), Escherichia coli (8, 2.2%) and Salmonella (6, 1.62%) were the most commonly isolated organisms respectively. While for urine samples, isolates were S. aureus (105, 28.37%) followed by E. coli from urine samples (62, 16.76%). During the study period, we observed there was a high degree of resistance to ciprofloxacin among Proteus spp (50%), E. coli (41.3%), S. aureus (20.6%), Klebsiella (20%) and Pseudomonas (20%). Government and stakeholders need to urgently develop antimicrobial stewardship programmes that will address the issue of antibiotic resistance in the country.